THE INFLUENCE OF MOTIVATION AND PERCEPTION AS PSYCHOLOGICAL FACTORS ON CONSUMER BUYING DECISION OF KAWASAKI NINJA MOTORCYCLE - Lomboan, Reynaldo; Saerang, David P.E.; Pangemanan, Sifrid S. (FEB Universitas Sam Ratulangi Manado, 2013)
Today, transportation is a human need for supporting their activities in every single day. In this modern era, all people are using sophisticated tools for their transportation. The increasing population in big cities make the companies in vehicle or automotive industry work hard to formulate their strategy. The congestion factors make people think to find a solution on how to avoid congestion interfere with their activities. Motorcycle then is an option to overcome the problems that interfere with their activities in terms of the bottleneck. Because of motorcycle can get rid of the discomfort in the jam. People started to think what kind of vehicle can avoid the traffic jam situation that make activities being disturbed. Motorcycle is the answer. People who have job that really needs the time efficiency have solved the common problem by purchasing motorcycle to get rid of the inconvenienceof being trapped in the crowdedtraffic. The specific objective of this research is to determine how motivation and perception influence on consumers buying decision of Kawasaki ninja motorcycle in Manado. The method of analysis used is Multiple Regression Analysis which enables to know the influence of independent variable on dependent variable. The result shows that motivation and perception influence consumers buying decision simultaneously and partially. Perception has the most influence to consumers buying decision.